NUT Carcinoma Resulting in SVC Syndrome. Issue 2 (4th March 2020) - Surro, Andrew; Al Tarhuni, Mohammed; Al-Katib, Sayf
Abstract : NUT ( nuclear protein in testis ) carcinoma is a poorly differentiated aggressive subtype of squamous cell carcinoma. NUT carcinoma is characterized by genetic rearrangements involving the NUT gene, resulting in the formation of oncogenic fusion proteins, most commonly NUT-BRD4. Originally described as a thymic carcinoma with NUT gene rearrangement in children and young adults, NUT carcinoma has been shown to occur in adults in a variety of locations. It is typically seen as an aggressive large soft tissue mass infiltrating adjacent structures. Because of the aggressive nature of NUT carcinoma, patients typically present in late stages of the disease and rapidly succumb to the disease. There are no pathognomonic, radiologic, or histopathologic features, and therefore NUT carcinoma is diagnosed via molecular assay, including a commercially available immunohistochemical assay. Additional molecular assays can be performed to demonstrate NUTM1 rearrangement and also to identify the oncogenic fusion protein. With more recent widespread availability of these assays, the reported incidence of NUT carcinoma is expected to increase. Prognosis remains poor for those diagnosed with NUT carcinoma, as there is no proven effective treatment. Recent research into the oncogenic fusion proteins driven by NUT rearrangement and clinical trials with targeted inhibitors offer hope for future therapy.